Identification of Shellfish Blue on an Ancient Egyptian (Dynasty XVIII) Painted Votive Textile - Jennifer Poulin; Margaret-Ashley Veall; Chris Paulocik (Heritage)
In 1906, Charles T. Currelly participated in excavations at Deir el-Bahri, Egypt, recovering votive offerings from the Temple of Hathor (Dynasty XVIII, reign of Hatshepsut, 1479–1458 BCE). These objects became part of the founding collection of the Royal Ontario Museum, where Currelly served as the first director. Among the offerings are several paintings on linen cloth. During examination of one painted textile, a border fringe with cream (suspected undyed), yellow and blue looped threads was sampled and analysed for dyes using gas chromatography–mass spectrometry. The yellow threads were found to contain a tannin-rich dyestuff, likely derived from Rhus spp., a common dye in ancient Egypt. Unexpectedly, the blue threads yielded brominated-indigoid marker compounds, indicating the use of a Murex-derived dye. While purple shellfish dye is rare due to the high cost of its complex production, blue shellfish dye is even more exceptional and has only been identified a handful of times on archaeological textiles. Calculated values of di-brominated to mono-brominated indigoid compounds suggests the dye originated from an indigotin-rich type of Hexaplex trunculus snail, a Mediterranean species. This finding represents a rare example of blue shellfish dye use in ancient Egypt and provides new insights into the dyeing technologies of Dynasty XVIII and the importance of this sky-blue colour in the worship of the goddess Hathor.